Producer organisations in an export-oriented value chain: What motivates small-scale farmers in Kosovo to collaborate? - Theresa Bäuml; Judith Möllers; Thomas Dufhues; Axel Wolz; Diana Traikova (European Countryside, 2022)
Producer organisations bear great potential to link small-scale farmers to markets. In post-communist economies, historically negative attitudes towards cooperatives are blamed as barriers to collaboration, but little is known about the broader range of motives to (not) cooperate. We use a structural equation model to analyse cooperation intentions in Kosovo's emerging export-oriented raspberry sector. In this context, negative images surrounding cooperation seem to belong to the past. Widespread positive attitudes towards joining producer organisations were driven by the wish to facilitate farm commercialisation. The most substantial influence on cooperation intentions came from the norms passed on by the family and farm advisory services. Yet, results beyond the econometric model show that a lack of information and knowledge and lack of institutional trust, mainly doubts about the feasibility of producer organisations, could hinder their spread and success. – – Organizatat e prodhuesve kanë potencial të madh për të lidhur fermerët e vegjël me tregje. Në ekonomitë me të kaluar komuniste, qëndrimet historikisht negative ndaj kooperativave fajësohen si barriera për bashkëpunim, por pak dihet për një gamë më të gjerë të motiveve për (mos)bashkëpunim. Ne përdorim një model të ekuacionit strukturor (structural equation model) për të analizuar synimet e bashkëpunimit në sektorin e mjedrës në Kosovë, një sektor në zhvillim dhe i orientuar drejt eksportit. Në këtë kontekst, imazhet negative rreth bashkëpunimit duket se i përkasin të shkuarës. Qëndrimet e përhapura pozitive ndaj anëtarësimit në organizatat e prodhuesve u shtynë nga dëshira për të lehtësuar komercializimin e fermës. Ndikimi më i rëndësishëm në synimet e bashkëpunimit erdhi nga normat e përcjella nga familja dhe shërbimet këshilluese bujqësore. Megjithatë, rezultatet përtej ekonometrisë tregojnë se mungesa e informacionit dhe njohurive dhe mungesa e besimit institucional, përkatësisht dyshimet mbi realizueshmërinë e organizatave të prodhuesve mund të pengojnë përhapjen dhe suksesin e tyre.
Keywords: 320; Kosovo; agricultural cooperatives; producer organisations; export-oriented value chain; raspberry production; smallholders; structural equation modelling; Kosovë; kooperativat bujqësore; organizatat e prodhuesve; zinxhiri i vlerës së orientuar nga eksporti; prodhimi i mjedrës; fermat e vogla; modelimi i ekuacionit strukturor